Student Well-Being in Higher Education: Insights from International Academic Mobility Experiences - GRIGORIȚĂ, Mălina-Elena (Studia Universitatis Babeș-Bolyai Psychologia-Paedagogia, 2026)
This qualitative study explores how Romanian university students perceive and describe institutional practices that foster student well-being based on their experiences during international academic mobility programs (e.g., Erasmus+). The study involved interviews with ten participants who completed academic exchanges in various European universities. The data were analyzed thematically to identify recurrent features of educational practices and institutional support systems that were perceived to positively impact students’ emotional, social, and academic well-being. The findings highlight several key aspects of effective practice abroad: personalized teacher-student relationships, accessible psychological counseling services, collaborative learning environments, and inclusive campus spaces designed to support mental health. Participants also reported a general culture of care and trust that encouraged autonomy, open communication, and a more human-centered approach to academic life. Many of these elements were either absent or less emphasized in their Romanian university context. This study offers concrete insights into transferable practices that may guide the development of more emotionally attuned, student-centered approaches in Romanian higher education. The results are relevant for institutional policymakers, educators, and university support services aiming to build a more holistic and evidence-informed approach to student well-being.